Detection of pleiotropic repeat expansions and their oligogenic contribution to amyotrophic lateral sclerosis - Hengeveld, Jennifer Christine (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
This thesis aims to advance our understanding of the genetic mechanisms that contribute to amyotrophic lateral sclerosis (ALS). The focus is on investigating pleiotropy in genetic contributors to ALS by examining the existence of multiple repeat expansions linked to other neurodegenerative diseases. Through these efforts, we hope to improve patient diagnosis and treatment by enhancing our knowledge of ALS risk genes. The first chapter of the thesis details the development of a polymerase chain reaction (PCR) panel for detecting intermediate repeat motifs in 35 neurodegenerative repeat expansion (NDREs) genes. This panel was created with the primary objective of simultaneously detecting multiple intermediate repeat expansions (RE) while preserving finite genomic DNA (gDNA) samples. This methodology is accurate, and results can be used in various studies, such as downstream bioinformatics, to enhance our understanding of neurodegenerative diseases. The aim of the second chapter in this thesis is to investigate the hypothesis that rare repeat expansions contribute to a significant proportion of ALS cases. To achieve this, we utilized the PCR panel developed in chapter 1 to measure 35 NDRE genes in >1500 ALS patients and >1700 controls from the Irish ALS DNA bank, which allowed us to improve upon earlier, underpowered studies that only examined some of the NDREs. Our study provides evidence for the potential involvement of several genes, such as C9orf72, FRA10AC1, ARX, and PABPN1, in determining ALS risk, disease duration, and site of onset in patients. However, replication and further research is needed to fully understand the implications of these findings and their potential for developing targeted interventions for ALS patients with varying clinical phenotypes. Following the genotyping of 35 NDRE genes in more than 1500 ALS patients and over 1700 controls from the Irish DNA bank, the aim of the third study in this thesis was to assess the individual-level burden of expanded repeats in NDRE genes in the Irish population with ALS. Our investigation focused on exploring the potential for additive oligogenic gene action and analysing the association between the number of repeat expansions and developing ALS, age of onset, and disease duration in the Irish population. The study revealed that the risk of developing ALS increases with the number of intermediate or long repeats in certain genes, with up to 5 expansions associated with a higher risk (p-value: 1.07?10-9). Our findings showed that the risk of developing ALS is influenced by the number of long repeat expansions, extending our understanding of the role of REs in ALS beyond the monogenic actions of specific genes such as C9orf72, ATXN2, or NIPA1. We also observed a statistically significant relationship between the number of repeat expansions and the age of onset (a decrease of 0.468 years) and disease duration (a decrease of 2.523 months), implying that individuals with a higher burden of expanded repeats may experience an earlier onset and a shorter disease duration. Finally, the last chapter explores the utility of Nanopore sequencing technology in generating long-read sequences for genotyping repeat expansions. A Cas9-enrichment protocol that does not rely on PCR amplification is used to evaluate the performance of this alternative approach. The study demonstrates the opportunities provided by signal-level analysis of individual sequence reads, suggesting that Nanopore experiments may be better suited for discovery of repeat expansions rather than accurate genotyping by conventional alignment/variant calling pipelines, and that combining multiple approaches may be necessary for comprehensive characterization of repeat expansions.
APPROVED
Keywords: ALS; Repeat Expansions